A qualitative study of customer experiences in the retail industry - Boudlaie, Hasan; Shahidi, Alemeh; Kenarroodi, Mohammadhosein; Keshavarz Nik, Behrouz (Technium Social Sciences Journal, 2020)
Customer experience (CX) is defined as the direct or indirect experience of a customer with organization, service, and facility processes, and how the customer interacts with the company’s services and other customers. There has not been much research on the concept of customer experience. Therefore, the purpose of this qualitative research is to understand what customer experience means in retail industry. The research data were collected through snowball sampling and interviews with 12 most recent consumers of Pajan dairy products. Next, collected data were coded, categorized and described; subsequently, conceptual map of the themes was drawn up. The main themes identified in this research are as follows: 1) Product familiarity; 2) Advertising; 3) Appearance of the product; 4) Taste and flavor; 5) Innovation and change; 6) Distribution channel; 7) Consultation; 8) Mindfulness of customers; 9) Entanglement of the customer with product; and 10) Product quality. Customer experience is a novelty in the field of marketing which researchers tried to cover its theoretical voids to some extent.